Strategi Pengembangan Keberagamaan Anak Autis Di SD Hikmah Teladan - Al-mansury, M.Nurkholiq Al-mansury; Nugraha N, Sri Wisnu (TarbiyahMU, 2025)
This article intends to explain the strategy for development of autistic children’s religiosity at Hikmah Teladan Elementary School. The method used is a case study. Based on analysis from various data sources (scientific journals, books, articles and current research), it is known that the development of children with autism is influenced by a number of factors that can play a role in the severity of symptoms and their progress, including the following: (1) genetic factors; (2) type and severity of Autism: (3) school and educational environment; (4) children's mental and emotional well-being; (5) the child's special needs and interests; (6) Physical health; (7) family support and (intervention and therapy. The strategies for developing the diversity of autistic children at Hikmah Teladan Elementary School include the following: Understanding the individual needs of autistic children, adapting teaching materials and methods, routines and structures, interactive activities and group therapy , Education for peers, Periodic assessment and evaluation, and Parental involvement.